Cyclical implications of minimum capital requirements - Frank Heid (Deutsche Bundesbank, 2005)
Capital requirements play a key role in the supervision and regulation of banks. The Basel Committee on Banking Supervision is now changing the current framework by introducing risk-sensitive capital charges. There have been concerns that this will unduly increase volatility in the banks' capital. Furthermore, when the credit supply is rationed, capital requirements may exacerbate an economic downturn. We examine the problem of cyclicality in a macroeconomic model which explicitly takes regulatory constraints into account. We find that the capital buffer which banks hold on top of the required minimum plays a crucial role in mitigating the volatility in capital requirements. Therefore, despite the fact that capital charges may vary significantly over time, the effects on the macroeconomy will be moderate.
Keywords: E32; G21; E44; 330; minimum capital requirements; regulatory capital; economic capital; capital buffer; pro-cyclicality; business cycle; bank lending channel; Eigenkapitalvorschriften; Wirtschaftspolitische Wirkungsanalyse; Bankbilanz; Makroökonomischer Einfluß; Theorie; Konjunktur